Wind turbine wake position detection and rotor speed-based wake steering validation in a wind tunnel wake simulator. Issue 5 (October 2020) - Castillo, Ricardo; Bayne, Stephen; Pol, Suhas; Westergaard, Carsten
Wind farm control has demonstrated power production improvements using yaw-based wake steering compared to individual turbine optimization. However, slower yaw actuation rates in response to rapid inflow changes lend to impracticality of yaw-based steering, as it causes time-varying downstream rotor–wake overlap, power production fluctuation, and consequent reduction. Therefore, closed-loop wake control is required to mitigate wake deflection uncertainty. To respond to rapid inflow variations, rotor speed actuated is investigated here. Furthermore, wake position information is required as feedback for closed-loop control function. For field-installed turbines, nacelle-based Light detection and ranging (LIDAR) is expected to provide this information. So far, LIDAR-derived wake position has been determined through model-based field reconstruction of scattered LIDAR data. However, this requires sophisticated, economically prohibitive LIDARs. To incorporate inexpensive, two-beam LIDAR for wake detection, a tip vortex-based approach was developed and is also presented here. These contributions can be considered as intermediate steps toward realization of a novel closed-loop wake control.